2016
DOI: 10.1021/acs.jctc.6b00994
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble-Average Representation of Pt Clusters in Conditions of Catalysis Accessed through GPU Accelerated Deep Neural Network Fitting Global Optimization

Abstract: We first report a global optimization approach based on GPU accelerated Deep Neural Network (DNN) fitting, for modeling metal clusters at realistic temperatures. The seven-layer multidimensional and locally connected DNN is combined with limited-step Density Functional Theory (DFT) geometry optimization to reduce the time cost of full DFT local optimization, which is considered to be the most time-consuming step in global optimization. An algorithm based on bond length distribution analysis is used to efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
211
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 139 publications
(218 citation statements)
references
References 55 publications
7
211
0
Order By: Relevance
“…The energetically most probable geometries for Pt 12 and Pt 13 are (a) and (j), respectively. These geometries are consistent with previous global optimizations based on density functional theory (DFT) by Zhang23, Da Silva24, Wei25, and Zhai26 et al ., which focused on obtaining a static global minimum geometry in each cluster size. Although it is difficult to obtain a global minimum with a single simulated annealing (SA) run, we can increase the precision when obtaining a global minimum geometry by performing multiple independent AIMD-SA runs.…”
Section: Resultssupporting
confidence: 91%
“…The energetically most probable geometries for Pt 12 and Pt 13 are (a) and (j), respectively. These geometries are consistent with previous global optimizations based on density functional theory (DFT) by Zhang23, Da Silva24, Wei25, and Zhai26 et al ., which focused on obtaining a static global minimum geometry in each cluster size. Although it is difficult to obtain a global minimum with a single simulated annealing (SA) run, we can increase the precision when obtaining a global minimum geometry by performing multiple independent AIMD-SA runs.…”
Section: Resultssupporting
confidence: 91%
“…In Figure 4A, we show the application of this approach to the equilibrium properties of the Pt 9 and Pt 13 clusters. 16 It has been demonstrated that not only the zero-point energies (from vibrational degrees of freedom) but also different spin multiplicities and point-group symmetries can make significant contributions to entropy and change the probability of isomer occurrence. This indicates that electronic, vibrational, and rotational degrees of freedom are all important in this description…”
Section: Cluster Isomer Diversitymentioning
confidence: 99%
“…16 The calculated heat capacity, which is sensitive to the isomer structure, can be different if fewer isomers are included.…”
Section: Cluster Isomer Diversitymentioning
confidence: 99%
“…Similar studies on varying Au configurations were also reported by Boes et al [99]. With a similar method, Zhai and Alexandrova developed a GPU-accelerated deep neural network (DNN) [32] for the global optimization of Pt 13 clusters [100]. To provide a general package for PES fitting, Khorshidi and Peterson developed an atomistic machine-learning package (Amp) combined with the new neural network representation shown above [101].…”
Section: Prediction Of Potential Energy Surfacementioning
confidence: 84%
“…(2) Similarly, with the rapid development of big data analysis and deep learning techniques [32], it is expected that they could be widely applied for catalytic activity predictions and global structural optimizations of catalytic systems. Though, so far, only a few relevant studies have focused on deep learning techniques (e.g., Zhai et al [100]), more applicable studies should emerge in the near future. It is also expected that some of the current challenges, such as CO 2 electroreduction selectivity and machine learning-assisted MD simulations, could be well-addressed and understood by state-of-the-art data-mining analysis and deep learning techniques.…”
Section: Remarks and Prospectsmentioning
confidence: 99%